MENINGKATKAN KUALITAS INTERAKSI SISWA DALAM DISKUSI KELOMPOK DI KELAS BAHASA INGGRIS MELALUI KEGIATAN LESSON STUDY - Erlin Erlin; Dyah Kusumastuti (Khazanah Pendidikan, 2019)
The application of lesson study is to improve the quality of student interaction in group discussions in English classes, it is carried out with the aim of improving the quality of communication and collaboration between students in solving problems or instructions given by the teacher. Furthermore, by having good communication and collaboration, it shows that the quality of interaction between students in discussions is also good. The Lesson Study was carried out in three stages, namely (1) Planning (Plan), (2) Implementation (Do) and (3) Reflection (See) with the object of observation of 8F grade students of MTs Muhammadiyah 01 Purbalingga with the total number of 36 students. The process of implementing lesson study is carried out in 2 cycles. The results of observation showed that in the learning process there was an improvement in the quality of student interaction in working in groups. This is indicated by the involvement of 3 groups of 6 groups that can complete the tasks given by the teacher with good communication and cooperation. Furthermore, in the second cycle the improvement in the quality of student interaction in discussion is getting better, this is indicated by the existence of 7 groups of 9 groups that can complete the task given by the teacher with good communication and collaboration between group members. As a percentage seen an improvement in the quality of student interaction in discussions by 27.7% of the percentage in the first cycle which only showed 50% and in the second cycle increased to 77.7%.Keywords: communication, collaboration, lesson study